2012
DOI: 10.1016/j.jcin.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Factors Associated With Percutaneous Coronary Intervention-Related Ischemic Stroke

Abstract: Ischemic stroke related to PCI is associated with potentially modifiable technical parameters. Careful procedural planning is warranted, particularly in patients at increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 22 publications
2
37
0
2
Order By: Relevance
“…This may be partially due to selection bias because MRI was performed in candidates for cardiac surgery for atherosclerotic disease. The rate of catheterization-related symptomatic ischemic stroke recorded in this study (0.24%) is roughly equivalent to those reported in previous studies [1][2][3][4][5][6][7][8][9].…”
Section: A Single Center Retrospective Analysis Of Catheterization-resupporting
confidence: 87%
See 1 more Smart Citation
“…This may be partially due to selection bias because MRI was performed in candidates for cardiac surgery for atherosclerotic disease. The rate of catheterization-related symptomatic ischemic stroke recorded in this study (0.24%) is roughly equivalent to those reported in previous studies [1][2][3][4][5][6][7][8][9].…”
Section: A Single Center Retrospective Analysis Of Catheterization-resupporting
confidence: 87%
“…Previous studies reported stroke rates of 0.1-0.4% [1][2][3][4][5][6][7][8][9]. Catheterization-related acute stroke is associated with high in-hospital mortality and prevalence of overall major complications [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Explanations could be a more severe vascular calcification in patients presenting with an ACS and a longer duration of the catheterization procedure during urgent or even emergency situations with possibly less careful advancement of catheters through the aorta under pressure of time, which is associated with an increased risk of cerebral embolization by scraping at aortic plaques. 9,22 Differences in plaque composition in ACS versus stable patients leading to an increased chance to cause embolism could also be 1 explanation for the findings. The possibility for hemodynamic compromise is also higher in patients with an ACS, which is known to increase the risk for intracardial thrombus formation and the risk for stroke.…”
Section: Discussionmentioning
confidence: 94%
“…Interventions at bypass grafts are usually technically more challenging, showing longer fluoroscopy times and, therefore, potentially leading to a higher risk of cerebral microembolism. 22 Especially in PCIs of internal mammary artery bypass grafts, which need to be intubated via the subclavian artery lying close to the internal carotid or vertebral artery, the risk of scraping at atherosclerotic plaques increases, potentially leading to a higher rate of cerebral embolism.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that it is associated with high in-hospital mortality [1][2][3][4] and causes life-changing disabilities in those who survive. [5][6][7] Previous studies were conducted in both single-centre 8,9 and multicentre settings 1,2 and reported the incidence, major determinants and outcomes of stroke after PCI.…”
mentioning
confidence: 99%